Conventional and Contemporary Arabic Language Teaching Methods: A Comparative Analysis - Mahbubi, Abdillah (Alsina : Journal of Arabic Studies, 2024)
This research aims to compare conventional and contemporary Arabic language learning methods in order to identify the advantages and disadvantages of each method. Conventional Arabic language learning usually focuses on a grammar-translation and rote memorization approach, which although effective in mastering grammatical rules, often pays little attention to practical communication skills. On the other hand, contemporary methods emphasize more on communicative approaches, the use of technology, and active participation of students in the learning process. This research uses comparative methods to analyze how these two methods are applied in various educational contexts. Data was collected through literature study. The research results show that each method has its own characteristics, advantages and disadvantages, where teachers can adjust the use of the method according to the conditions and material being taught.